The Application of Inorganic Nanoparticles in Molecular Targeted Cancer Therapy: EGFR Targeting - Sun, Meng; Wang, Ting; Li, Leijiao; Li, Xiangyang; Zhai, Yutong; Zhang, Jiantao; Li, Wenliang (Frontiers in Pharmacology, 2021)
Epidermal growth factor receptor (EGFR) is an anticancer drug target for a number of cancers, such as non-small cell lung cancer. However, unsatisfying treatment effects, terrible side-effects, and development of drug resistance are current insurmountable challenges of EGFR targeting treatments for cancers. With the advancement of nanotechnology, an increasing number of inorganic nanomaterials are applied in EGFR-mediated therapy to improve those limitations and further potentiate the efficacy of molecular targeted cancer therapy. Given their facile preparation, easy modification, and biosecurity, inorganic nanoparticles (iNPs) have been extensively explored in cancer treatments to date. This review presents an overview of the application of some typical metal nanoparticles and nonmetallic nanoparticles in EGFR-targeted therapy, then discusses and summarizes the relevant advantages. Moreover, we also highlight future perspectives regarding their remaining issues. We hope these discussions inspire future research on EGFR-targeted iNPs.